2022
DOI: 10.53713/nhs.v2i2.70
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Personal Protective Equipment Compliance among Midwives During COVID-19 Pandemic in Indonesia

Abstract: Individuals most at risk of infection are those who are in close contact with COVID 19 patients, such as midwives who run Independent Practices. Midwives can protect themselves when providing care by complying with infection prevention and control practices that include proper administrative, environmental and engineering control and use of Personal Protective Equipment (PPE) (i.e. appropriate in the selection of the appropriate type of PPE, how it is used, how to release and how to dispose or wash PPE). So re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The researcher argues that parents' readiness is good because the COVID-19 pandemic has occurred for two years, so parents already have sufficient information and experience in preventing the transmission of COVID-19. The readiness implementation of good health protocols can also be affected by regulations that force everyone to be disciplined in play health protocols (Leli et al, 2022) The availability of facilities and infrastructure also supports good preparedness. Adequate facilities and infrastructure are available from sufficient financial abilities.…”
Section: Results Respondents' Characteristicmentioning
confidence: 99%
“…The researcher argues that parents' readiness is good because the COVID-19 pandemic has occurred for two years, so parents already have sufficient information and experience in preventing the transmission of COVID-19. The readiness implementation of good health protocols can also be affected by regulations that force everyone to be disciplined in play health protocols (Leli et al, 2022) The availability of facilities and infrastructure also supports good preparedness. Adequate facilities and infrastructure are available from sufficient financial abilities.…”
Section: Results Respondents' Characteristicmentioning
confidence: 99%
“…In a study by Polovich and Clark (2012), 89% of nurses stated that written protocols about safe handling precautions of ADs are available in their institutions but did not reflect current guidelines. Engineering controls and administrative controls are part of the hierarchy of controls that can lower worker occupational exposures and reduce the risk of illness/injury (Leli, Kundaryanti & Novelia, 2022). When compared with the literature, the institutions involved in this study were considered to be at a very good level in terms of engineering controls (BSC) and administrative controls (written policy and guidelines).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is present in the conjunctiva and can enter the respiratory tract through the nasolacrimal duct (Ho et al, 2020). Efforts to prevent COVID-19 transmission by using Personal Protective Equipment (PPE) such as medical masks and eye protectors, a previous study reported by 63 respondents, 47 (74.6%) respondents obediently used PPE, and 16 (25.4%) respondents did not comply with the use PPE (Nurleli et al, 2022). This literature review aimed to describe ocular transmission as an alternative route of COVID-19 transmission.…”
Section: Introductionmentioning
confidence: 99%